The Failing Structures of Animal Health Services: Room for Improvement - Nellemann Kryger, Karsten (2006)
If Governments and donors are primarily preoccupied with containing the risk of a human pandemic there are serious doubts that the results of the commotion around avian flu will significantly improve smallholder poultry producers’ access to animal healt